1978
DOI: 10.1126/science.204005
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Function of Michigan Dairy Farmers Exposed to Polybrominated Biphenyls

Abstract: Michigan dairy farm residents ate farm products containing polybrominated biphenyls (PBB's) after the accidential contamination of animal feed with the chemical in that state in 1973. The circulating blood lymphocytes of these residents show significant changes. Abnormalities include decreases in the numbers and percentages of peripheral blood lymphocytes that form rosettes with either sheep erythrocytes alone or with sheep erythrocytes sensitized with antibody and complement, increases in lymphocytes with no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(18 citation statements)
references
References 4 publications
0
17
0
1
Order By: Relevance
“…Some older data are available (Bekesi et al 1978) on farmers with very high accidental exposure to polybrominated biphenyls (PBBs). Although it is questionable whether this polybrominated substance produces immunological effects identical to those caused by TCDD (and the exposure was against a mixture of several congeners) and although the methods used were different, the decrease in the percentage of peripheral blood lymphocytes that form rosettes with sheep erythrocytes, as well as the increase in lymphocytes with no detectable surface marker ("null" cells) observed by these authors might indicate some similarity with our data.…”
Section: Possible Significance Of the Data Possible Mode Of Action Anmentioning
confidence: 99%
“…Some older data are available (Bekesi et al 1978) on farmers with very high accidental exposure to polybrominated biphenyls (PBBs). Although it is questionable whether this polybrominated substance produces immunological effects identical to those caused by TCDD (and the exposure was against a mixture of several congeners) and although the methods used were different, the decrease in the percentage of peripheral blood lymphocytes that form rosettes with sheep erythrocytes, as well as the increase in lymphocytes with no detectable surface marker ("null" cells) observed by these authors might indicate some similarity with our data.…”
Section: Possible Significance Of the Data Possible Mode Of Action Anmentioning
confidence: 99%
“…In 1978, the immunotoxic potential of PBBs was identified in humans, in a follow-up study to the Michigan accident (Bekesi et al 1978). A 1979 hazard assessment of PBBs done by the US Environmental Protection Agency showed that they were teratogenic, embryotoxic, and immunosuppressive in mice and rats, and carcinogenic in rats (OECD 1994).…”
Section: Brominated Flame Retardantsmentioning
confidence: 99%
“…In none of the three studies were serum PBB or PCB levels associated with overt adverse health effects. However, immunologic studies on a subset of the exposed population in Michigan were conflicting, with an early study showing decreases in T-cell function, as measured by E-rosette formation, and increases in number of null cells (269), but a subsequent study failed to confirm this result (268).…”
Section: Contamination Of Water Suppliesmentioning
confidence: 92%